Analysis of Arabic Textbook Lisānul Jāmi’ah: Gender Perspective - Ulfa, Arifah; Jaeni, Muhamad; Priyatun, Inayah (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
In the preparation of textbooks, it is necessary to pay attention to the content of the material so that it is in accordance with socio-cultural elements without causing multiple interpretations and an imbalance. The issue of gender is one of the social elements that can be influenced by the educational environment. This includes the learning process and Arabic language textbooks. While Arabic is one of the foreign languages whose language system is very gender biased. So in the preparation of Arabic textbooks, you must be more careful in order to minimize the existence of gender bias in textbooks. This also applies to the Arabic language textbook Lisanul Jami’ah I. This research is entitled Analysis of the Lisānul Jāmiʻah I Textbook Gender Perspective with the formulation of the problem how to analyze the gender perspective in the Lisānul Jāmiʻah I Arabic textbook and how the content of gender bias in the Lisānul Jāmiʻah I Arabic textbook I. The purpose of this research is to find out the analysis of the Arabic language textbook Lisānul Jāmiʻah I from a gender perspective to determine the content of gender bias. The purpose of this research is to provide contributions, references, considerations and insights related to gender in textbooks. This type of research is library research with data sources taken from primary and secondary data sources. Sources of data collected by documentary and interview techniques. While the data analysis using content analysis techniques. The results of this study indicate that most of the contents of the Lisānul Jāmiʻah I textbooks have shown to be gender sensitive. However, the content of gender bias is also quite a lot, although not as much as the content of gender sensitive. In this textbook, gender-neutral content of the textbook is also found.